Anti-BP180 Autoantibodies Are Present in Stroke and Recognize Human Cutaneous BP180 and BP180-NC16A - Wang, Yanan; Mao, Xuming; Wang, Di; Hammers, Christoph M.; Payne, Aimee S.; Wang, Yiman; Jin, Hongzhong; Peng, Bin; Li, Li (Frontiers in Immunology, 2019)
Objective: Current evidence has revealed a significant association between bullous pemphigoid (BP) and neurological diseases (ND), including stroke, but the incidence of BP autoantibodies in patients with stroke has not previously been investigated. Our study aimed to assess BP antigen-specific antibodies in stroke patients. Design: 100 patients with stroke and 100 healthy controls were randomly selected for measurement of anti-BP180/230 IgG autoantibodies by enzyme-linked immunosorbent assay (ELISA), salt-split indirect immunofluorescence (IIF) and immunoblotting against human cutaneous BP180 and BP180-NC16A. Results: Anti-BP180 autoantibodies were found in 14(14.0%) patients with stroke and 5(5.0 %) of controls by ELISA (p<0.05). Sera from 13(13.0%) patients with stroke and 3(3.0 %) controls reacted with 180-kDa proteins from human cutis extract (p<0.05). 11(11.0%) of stroke and 2(2.0 %) of control sera recognized the human recombinant full length BP180 and NC16A (p<0.05). The anti-BP180-positive patients were significantly younger than the negative patients at the time of stroke (p<0.001). Conclusion: Development of anti-BP180 autoantibodies occurs at a higher frequency after stroke, suggesting BP180 as a relatively common autoantigen after stroke and providing novel insights into BP pathogenesis in aging.